Appropriateness of Transcatheter Aortic Valve Replacement: Insight From the OCEAN-TAVI Registry. Issue 4 (April 2020) - Inohara, Taku; Vemulapalli, Sreekanth; Kohsaka, Shun; Yashima, Fumiaki; Watanabe, Yusuke; Shirai, Shinichi; Tada, Norio; Araki, Motoharu; Naganuma, Toru; Yamanaka, Futoshi; Ueno, Hiroshi; Tabata, Minoru; et al.
Abstract : Background: Transcatheter aortic valve replacement (TAVR) is widely used; however, its appropriateness is unknown. We sought to investigate the appropriateness of TAVR. Methods and Results: We assigned appropriateness ratings to patients undergoing TAVR for severe aortic stenosis between October 2013 and May 2017 at 14 Japanese hospitals participating in the optimized transcatheter valvular intervention-transcatheter aortic valve implantation registry according to the US appropriate use criteria for treating severe aortic stenosis. To account for the influence of uncaptured variables on appropriate use criteria ratings, we initially assigned them to a best-case scenario where they were assumed to classify a case to the most appropriate clinical scenario and then to a worst-case scenario where assumed least appropriate. Overall proportion of TAVRs classified as appropriate, maybe appropriate, or rarely appropriate was assessed. In addition, extent of hospital-level variation in rarely appropriate procedures was evaluated. Of 2036 TAVRs (median age [25th, 75th]: 85.0 years [81.0–88.0]; 70.5% female the Society of Thoracic Surgeons Predicted Risk of Mortality score: 6.2% [4.4–8.9]), in the best-case scenario, 177 (8.7%) were not successfully mapped, and 1580 (77.6%) were classified as appropriate, 180 (8.8%) as maybe appropriate, 99 (4.9%) as rarely appropriate, respectively. In the worst-case scenario, the rate of rarely appropriate increased to 6.8%. The majority of rarely appropriate TAVRs was performed in patients with moderate to severe dementia (defined as mini-mental status examination of ⩽17), bicuspid aortic valve, or anticipated life expectancy <1 year. There was substantial variation in the proportion of rarely appropriate TAVR across hospitals (median rate of rarely appropriate: 4.9% [3.8–6.6] in the best-case scenario, P <0.001; 6.5% [5.6–8.6] in the worst-case scenario, P <0.001). Conclusions: In clinical practice, the proportion of rarely appropriate TAVRs ranged from 4.9% to 6.8% with substantial institutional variation. Our study elucidates common clinical scenarios deemed rarely appropriate and clarifies the potential targets of quality improvement. Registration: URL: https://www.umin.ac.jp/ctr/index.htm . Unique identifier: UMIN000020423. Abstract : Supplemental Digital Content is available in the text.